Speech technology applied to children with speech disorders (2008)
This paper introduces an informatic applications for speech therapy in Spanish language based on the use of Speech Technology. The objective of this work is to help children with different speech impairments to improve their communication skills. Speech technology provides methods which can help children who suffer from speech disorders to develop pre-Language and Language. For pre-Language development the informatic application works on speech activity detection and intensity control, and for Language the application works on three levels of language: phonological, semantic and syntactic. This application is designed to enable those suffer from speech disorders to train their communication capabilities in an easy and entertaining way. This tool is available for free distribution.